Reassessing EU comparative advantage: The role of technology - Filippo Di Mauro; Marco Matani; Gianmarco I. P. Ottaviano (Halle Institute for Economic Research (IWH), 2024)
Based on the sufficient statistics approach developed by Huang and Ottaviano (2024), we show how the state of technology of European industries relative to the rest of the world can be empirically assessed in a way that is simple in terms of computation, parsimonious in terms of data requirements, but still comprehensive in terms of information. The lack of systematic cross-industry correlation between export specialization and technological advantage suggests that standard measures of revealed comparative advantage only imperfectly capture a country's technological prowess due to the concurrent influences of factor prices, market size, markups, firm selection and market share reallocation.
urn:nbn:de:gbv:3:2-1101499
Keywords: B17; C19; C51; C80; D21; D43; F02; F12; F14; F61; L13; L25; O49; 330; comparative advantage; European cross-country data; firm heterogeneity; international trade; monopolistic competition; multi-product firms; productivity